Influence of Curricular and Co-Curricular Activities on Academic and Social Skill Development in Elementary Students: A Study - Pal, B.K.; Malhotra, Karishma; Kumar, Anjani; Sunder, Shyam; Sharma, Sharad; Suman, Suman (Journal of Neonatal Surgery, 2025)
This study investigates the impact of curricular and co-curricular activities on fostering academic and social competencies among elementary school students. Employing a descriptive survey design, the research involved 60 students from public and private elementary schools. A researcher-designed five-point Likert scale, comprising 20 items (11 assessing academic skills and 9 evaluating social skills), was administered to the participants. The scale included 18 positive and 2 negative statements. Findings indicate that both curricular and co-curricular activities significantly contribute to the development of academic and social skills, equipping students for future success. Statistical analysis revealed no significant differences in skill development across gender, school type (public vs. private), or family structure (nuclear vs. joint). These results underscore the universal benefits of such activities in elementary education